PERBANDINGAN PENGGUNAAN FILLER SEMEN DENGAN FILLER KAPUR PADA KARAKTERISTIK CAMPURAN AC-WC AKIBAT PENGARUH MASA PERENDAMAN AIR - Sasongko, Riyan Nur (Jurnal Civil Engineering Study, 2023)
Roads are one of the most essential transportation infrastructure for the advancement of public welfare and life improvement. As for an attempt to improve the quality of road pavement (asphalt), one of them is by adding fillers or fillers of cement and lime to get good quality asphalt pavement. This research will add filler with a percentage of cement and lime filler ranging from 0%, 5%, 10%, and 15%, and there is also a soaking period of the samples that will be made with this percentage with a sample soaking period ranging from 0 to 3 days of soaking period to know the effect of the soaking period on the strength of the asphalt bricks sample with these percentage variations. Using the marshall quiotient method, the results obtained that asphalt with additional cement filler is still within specifications, while for asphalt soaking with lime filler experiences high stiffness and cracks easily